Nilai-nilai Pendidikan Akhlak dalam Novel Bidadari Bermata Bening Karya Habiburrahman El Shirazy - Safitri, Wulandari; Rahman, Rini (ANWARUL, 2023)
Islamic education is inextricably linked to the religion's name, core principles, and laws governing daily life. The persistent moral dilemma is thought to be something that education can resolve. Morality and religion are inextricably linked in Islamic education and cannot be separated. The principles of moral education can be found not only in formal education but also in extracurricular pursuits like attending mosque sermons, watching movies, and learning about Islamic educational principles from other literary works like novels. The book Bidadari Bermata Bening served as the research's primary source of data. This study tries to clearly identify the moral principles that Allah SWT upholds in Habiburrahman El Shirazy's novel Bidadari. This research approach is hermeneutic and qualitative. This kind of investigation is done at libraries. The findings of this study include moral principles that Allah SWT should uphold. These principles include asking Allah SWT for pardon, abstaining from immoral behavior, showing gratitude to Allah SWT, and developing positive attitudes toward Allah SWT.